Edukasi Etika Bisnis dan Investasi Syariah Bagi Pengelola dan Anak Asuh Yayasan Islamadina - Aji, Tony Seno; Isbanah, Yuyun; Kistyanto, Anang; Witjaksono, Andre Dwijanto; Budiono, Budiono (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2018)
ABSTRACT The orphanage's foundation has largely begun to grow the business. This is a form of development of financial independence. Orphanages no longer fully expect funding from donors. In line with the above, the ability to manage ethical business and selection of sharia investment alternatives need to be understood by foundation managers and residents of orphanages. Training implementation methods using lecture, discussion, test, and simulation techniques. Training is carried out in two stages. The first stage of learning business ethics and sharia investment. The second stage is the simulation of investment instrument transactions. The target to be achieved is the acquisition of knowledge of managers / administrators and residents of orphanages related to business ethics and sharia investment instruments. Education of Business Ethics and Sharia Investment for the Managers and residents of Yayasan Islamadina was held on October 15, 2017. The activity was attended by 41 people. The results of the evaluation show that the level of satisfaction of the training and the ability of the resource persons are included in the high category. The results of the activities increased participants' understanding of business ethics and sharia investment instruments between before and after the training. This is demonstrated by the Wilcoxon Test results which show there are differences in pretest value with the posttest value, the conclusion there is increasing participants' understan.ding of the business ethics and sharia investment instruments between before training with after training Keywords: Islamic Business Ethics, Sharia Investment, Investment Instrument